Coal fly ash-derived zeolite for efficient ammoniacal nitrogen removal from freshwater pearl farming wastewater - Bo Xia; Honghao Chen; Juntao Wang; Xiaocheng Pan (iScience)
Summary: Freshwater pearl farming in China generates wastewater high in ammoniacal nitrogen (NH₃-N) posing environmental threats. This study explores the use of coal fly ash (CFA), an industrial waste, to synthesize A-type zeolite for effective NH₃-N removal from pearl farming wastewater. The zeolite was prepared via pickling pretreatment and hydrothermal methods, resulting in a material with favorable adsorption properties, including cubic and spherical microstructures, a specific surface area of 17.5 m2/g, an average pore size of 10.7 nm, and a pore volume of 0.03 cm³/g. Adsorption experiments showed that NH₃-N removal followed pseudo-first-order kinetics and fit the Dubinin-Radushkevich isotherm model. Applied to actual wastewater, the zeolite achieved a 74% removal efficiency at a dosage of 70 g/L. This approach converts CFA into a valuable adsorbent, reducing its environmental impact, and enhances the sustainability of freshwater pearl farming through effective wastewater treatment, and demonstrates the potential of transforming industrial waste into functional materials for environmental remediation.